Composite overwrap repair of pipelines-reliability based design framework. (June 2022) - Saeed, Nariman; Kang, Won-Hee; Samali, Bijan
Abstract: Considering the ages and need for repairment of the gas and oil transmission pipes in the world, in the past years, lab and field experiments were performed on fiber reinforced polymer (FRP) wrapping to steel pipes. Although this technology has widely been employed for decades, further improvement on the design guidelines is still needed. In this context, this study proposes a reliability structural design framework for the repairment of corroded pipelines using FRP composite wrapping. To be consistent with international structural design standards, reliability-based design framework is to be proposed within a semi-probabilistic approach by calibrating safety factors to account for the associated uncertainties in capacity and load effects to best meet the cost-safety balance in design. Currently, the repair design practice for corroded pipelines is based on a deterministic approach, and it cannot ensure the proper consideration of uncertainties and meeting a consistent level of target reliability in design. This study involves comprehensive experiments of FRP materials under two different environmental conditions for onshore and offshore pipes, which were used to propose the best-fit statistical models to the design parameters to realistically represent the random variables in the proposed safety factor based structural design framework. Through extensive reliability analyses, the values for the safety factors for composite and steel have been proposed according to the target reliability indices and the corrosion rate. The proposed design framework for corroded steel pipes with FRP overwrap repairment is expected to improve the current design practice and optimize the cost and safety by meeting the target reliability level.